TRANSFORMETION OF WAR THROUGH THE PRISM OF ASYMMETRY (Annual of the Faculty of Philosophy in Skopje, 2014)
In general, it would be best for armed forces of the West to prepare conventional and to adapt for unconventional The conclusion that civilized will prevail over barbarians does not mean that they neglect the unconventional threats and strategies. Ultimately, such strategies and threats not necessaiy help the Barbarians to win, but can still cause quite a damage, pain and distraction. The more important, if they are used by civilized occasionally as small skirmishes preceding the battle, then they can help in establish a setting in which victory becomes possible or likely than defeat. On the other side, nether the historical superiority of civilized and recent experiences in the former Yugoslavia, Iraq and Afghanistan shows that adaptability of the forces of West for unconventional, can make mxe advanced one to feel complacent. Complacency in a world where there is a weapon of mass destruction is undesirable.The Western way of war in which the desire is to limit the war on professional fighters, points to a decisive victory on the battlefield. But the experience of modern wars and conflicts show that modern war requires more interaction with civilians and consequently is not always possible to distinguish fightersfrom civilians. Regardless of the intentions of the parties, it'll be extremely difficult to prevent spillover of military conflict on civilians. Although behind military low stands a moral, a political and a humanitarian dimension, still there going to be performed attacks on facilities containing dangerous powers or facilities that are necessary for the survival of the civilian population. Such attacks are justified by the need of dismantling the armed forces of the enemy. The ability to circumvent the civil disturbances that would stand in the way of a victory would possess just the most advanced armies. When a country faces defeat in a conventional war, the attack on the opponent 's society - is the only and the last opportunity that remains. All this explains why the war in the 21st century will be daunting for those who are convinced that the dominant armed forces can be used to in decisive way without its effect triggering the appropriate way of revenge.
Keywords: ASYMMETRY; THREATS; STRATEGY; TRANSFORMATION; TECHNOLOGIES